Pastoralists are Peoples: Key issues in Advocacy and the Emergence of Pastoralists' Rights. (1st January 2017) - Bassi, Marco
Abstract : This article deals with the rights-based approach to development that in the last decade has informed discourse on pastoralism. It focuses on the organisations that have engaged in pastoral advocacy at the global level, considering the dynamic conceptions of development, human rights and policy that provide their cultural and operative background. It outlines the convergence of indigenous rights with the core challenges of pastoralism, and the emergence of the new concept of 'pastoralists' rights', eventually considered as a separate domain. It argues that the mobility paradigm of pastoral development may not by itself provide an adequate answer to the problems of pastoral communities, unless explicit consideration is made of the collective and procedural rights recognised under the international human rights framework.